The Impact of Negative Family Communication on Children's Psychology (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Child rearing is a core feature of families : it shapes not only the child entity but also the fluidity and unity in a home. PARENT-CHILD COMMUNICATION Parent-child communication is essential in the development ofchildren’s adult emotional, social and cognitive lives. From the manners, behavior, and interactions that a child demonstrates they have an opportunity to learn about the family the child belongs to. They may give information of the kind of environment the child is in as well as the challenges that surround the social growth of that child.Indeed, as this article shows there is need for parents to accord communication the concern it deserves out of discipline practices. Cordial, stable, and compassionate communication fosters, and improves the cooperation and compassion between parents and children, and thus children feel a part of the family. More pointedly, the article also gives a warning on child participation in domestic battle. Observing parent conflict and divorcing parents puts a child at risk for developing undesirable psychological conditions such as anxiety or a weakened self esteem or they are likely to pursue unhealthy relationships when they grow up.Thus parents by avoiding negativity in communication, by protecting children from stress due to conflict not only improve children’s present quality of life but also provide them with necessary tools to avoid or cope with future interpersonal problems. As such, early family communication patterns play a critical role in shaping healthy thinking individuals and therefore, foster healthy thinking citizens in a society.